O jogo teatral para a formação do professor: uma análise do currículo acadêmico do curso de pedagogia da FACED – UFAM - Araújo, Lorena Viana de (Brasil, 2023)
Through an approach about the pedagogical action, this research sought as a general objective to analyze and understand how the work with theatrical games is structured within the curriculum of the faculty of education at the Federal University of Amazonas. An analysis was carried out on the syllabi, curricula and pedagogical proposals, aligned with a contextualization of the references that address the subject, so that in the end it could be highlighted how the structuring of the curriculum with theatrical games occurs within the scope of the syllabus of the faculty of education from the Federal University of Amazonas. The structuring of this research takes place through a bibliographical analysis of references and guiding documents of the course and consolidates itself in a theoretical observation in context as the one that emphasizes the specialized literature in the approached subject. This effort results in the perception of the challenges in working with artistic disciplines that support an approach to theatrical games in the context of teacher education.